Social Support In Pesantren In Shaping Santri's Religious Moderation Identity: An Analysis Based On Social Identity Theory - Suyuthi, Ahmad Fuad Hasyim Hafid; Ma'arif, Syamsul; Nurhadi, Agus; Wijaya, Roma (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study investigates the significant role of social support within pesantren in shaping santri's religious moderation identity. The escalating global challenges to religious harmony highlight the critical need to cultivate a balanced, tolerant, and inclusive understanding of Islam, particularly among the youth. Pesantren, as traditional Islamic educational institutions in Indonesia, possess immense potential in fostering such an identity. While qualitative studies have broadly acknowledged this role, there is a distinct lack of systematic quantitative research specifically analyzing the multi-dimensional aspects of social support—from educators, peers, and institutional policies/culture—and their direct impact on santri's religious moderation identity, particularly when framed by Social Identity Theory. This research, conducted in selected pesantren in Karesidenan Kedu, Central Java, employed a quantitative approach with a correlational design. Data from 380 santri were collected using a structured questionnaire via simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all dimensions of social support within pesantren—namely, support from educators, support from peers, and support from pesantren policy and culture—each have a significant positive influence on santri's religious moderation identity. This indicates that the comprehensive social ecosystem within pesantren profoundly shapes santri's self-identification as moderate, their openness to diverse religious views, and their rejection of extremism. The research contributes empirical evidence to Social Identity Theory, demonstrating its applicability in understanding religious identity formation within traditional educational settings, and provides practical implications for pesantren management to strategically enhance these social support mechanisms for fostering stronger moderate religious identities among santri.